Strategi Pengembangan Ekonomi Pada Pedagang Angkringan di Kota Jember (Lembaga Pengembangan Kinerja Dosen, 2023)
After going through a long stage of progress, the economic aspect in conclusion has come to the degree of innovative economy. A situation where various business opportunities are wide open and creativity is a determining aspect of the development of this economic zone. This paper examines developments and innovative economic development strategies through culinary endeavors raised by angkringan traders in Jember City. This research uses a descriptive qualitative research approach, namely with the meaning of understanding events about what is felt by research subjects such as actions, attitudes, assumptions and others. Research results prove that the development of this angkringan business is driven by the will of the authorities and local residents to create an activity square. In its development, the culinary efforts of these angkringan traders experienced an increase, resulting in an important impact on economic development and family safety. Some of the business actors who have been in the culinary business for a long time already have a large income, which affects their social life. Even so, this effort has faced setbacks, as a result affecting the economic situation of the families of the traders.